2020
DOI: 10.1038/s41598-020-68430-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and comparing postoperative infections in different stratification following PCNL based on nomograms

Abstract: To discuss the mechanisms of infection complications in different degrees after percutaneous nephrolithotomy (pcnL) through predicting and comparing post-pcnL infections based on nomograms, a retrospective cohort study was conducted among 969 cases who underwent PCNL from Dec 5, 2016 to Dec 25, 2017 in Kunming, Yunnan Province. We examined clinical features, urine routine, blood routine, blood biochemistry, imaging studies and operative information and recorded the examination results before surgery for univar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A study by Erdogan et al reached similar conclusions [ 15 , 16 ]. Many studies have focused on finding risk factors for complications of SIRS and sepsis after PNL [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ], including female sex, diabetes mellitus, volume of renal stones, degree of hydronephrosis, density of hydronephrosis, urinary leukocytes, positive urine cultures and elevated blood neutrophils. There is still no precise stratified scoring system or comprehensive model to predict preoperative calculous obstructive pyonephrosis before PNL.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Erdogan et al reached similar conclusions [ 15 , 16 ]. Many studies have focused on finding risk factors for complications of SIRS and sepsis after PNL [ [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ], including female sex, diabetes mellitus, volume of renal stones, degree of hydronephrosis, density of hydronephrosis, urinary leukocytes, positive urine cultures and elevated blood neutrophils. There is still no precise stratified scoring system or comprehensive model to predict preoperative calculous obstructive pyonephrosis before PNL.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al have found that preoperative Cr level and positive pre-operative multidrug-resistant (MDR) urine culture were independent risk factors in patients with struvite stones following PNL (18). Jiang et al have identified positive urine culture, serum calcium, and urine pH that were significantly connected with the incidence of sepsis after PNL (19). Moreover, Ozgor and his colleagues demonstrated that patients with ≤40 years old, operation time ≥60 min, and presence of renal abnormality were remarkably associated with infectious events following fURS (16).…”
Section: Discussionmentioning
confidence: 99%
“…nephrolithometry score; SFR S.T.O.N.E. Yes Graphic chart Smith et al [ 10 ] CROES score; SFR Stone burden, stone location, number of stones, and surgical volume Yes Graphic chart Jeong et al [ 11 ] S-ReSC; SFR Pelvi-caliceal system subdivided in nine separate locations, each location corresponding to 1 point Total score: cumulative sum of involved locations Yes Computed tomography imaging Xun et al [ 24 ] Urosepsis in general population Albumin-globulin ratio, leukocytosis, positive urine culture, and female sex No Graphic chart Jiang et al [ 25 ] Post-operative fever, SIRS, sepsis in general population Post-operative fever: leukocyturia and urine nitrite SIRS: positive urine culture, positive urine nitrite, and operation time Sepsis: positive urine nitrites, urine pH, positive urine culture, serum calcium, and operation time No Computer software and graphic chart Wang et al [ 26 ] Urosepsis in general population Presence of staghorn stone, pre-operative urine culture, and pre-operative nephrostomy No Graphic chart Gu et al [ 28 ] Urosepsis in general population Presence of urine nitrite, positive urine culture, intra-operative hypotension, and staghorn stone No Graphic chart Liu et al [ 27 ] Urosepsis in general population White blood cell count, presence of urine nitrites, positive urine culture, staghorn stone, and complete stone clearance No Graphic chart Zeng et al [ 29 ] Venous thromboembolism …”
Section: Methodsmentioning
confidence: 99%